PERTIMBANGAN YURIDIS PENYIDIK DALAM MENGHENTIKAN PENYIDIKAN PERKARA PELANGGARAN KECELAKAAN LALU LINTAS DI WILAYAH HUKUM POLRESTA JAMBI - Islah Islah (Universitas Batanghari Jambi, 2016)
A high accident rate makes investigators do not process all the events , but nothing stopped the investigation of course no juridical considerations in this regard besides humanitarian consideration also the interests of justice for the people of IndonesiaKeyword : high accident, juridical consideration